Caracterización del comportamiento fenológico de portainjertos en morfotipos de chirimoya (Annona cherimola Mill.) de la provincia de Loja, bajo invernadero - Buri Buri, Juan Andrés (2019)
One of the most diverse cherimoya tree centers (Annona cherimola Mill.) is located between south Ecuador and north Peru, in territories located between 1,000 a 2,500 m. a. s. l. Ecuador has about 1,000 ha of cherimoya trees, mainly distributed in Guayllabamba, Tumbaco, Gualaceo, Paute, and Patate. However, production in these places does not go over 1,000 kg/ha. Research into this species is mostly oriented to origin, morphological molecular and physiological characterization, although limited in the field of the species spreading with commercial purpose. This is the reason why this research studied the phenologic behavior of cherimoya tree morphotypes Lisa (Y025), Umbonata (Y004), Impresa Simple (Y022), Lisa (T009), Mamillata (T016), Impresa Simple (T030), Umbonata (T036) e Impresa Doble (T006), from Tacoranga y Nangora. The test took place in the Germoplasm Bank of the National University of Loja, using an absolutely random design (ARD). The variance analysis (ANOVA) and the Pearson correlation were carried out using Infostat software, version 2018. Cherimoya trees presented six sequence states between germination and surfacing: A. Hypocotyl appearance; B. Swan neck hypocotyl; C. Hypocotyl surfacing and seminal cover; D. Seminal cover falling; E. Completely formed plant; F. Seedling with optimal characteristics to graft. The germination type observed was epigeal cryptcotyle, where the seminal covers raise together with the cotyledon during surfacing. The highest percentage of graft root taking was obtained with the following morphotypes: Impresa Doble (T006), Mamillata (T016), Umbonata (Y004), Impresa Simple (T030), and Umbonata (T036) with 77 %. Key words: Annona cherimola Mill., Phenology, Morphotypes, Port grafting.